Use of health services according to income before and after elimination of copayment in Germany and restriction of universal health coverage in Spain - Lourdes Lostao; Siegfried Geyer; Romana Albaladejo; Almudena Moreno-Lostao; Elena Ronda; Enrique Regidor (BMC, 2018)
Abstract Background In Germany copayment for medical consultation was eliminated in 2013, and in Spain universal health coverage was partly restricted in 2012. This study shows the relationship between income and the use of health services before and after these measures in each country. Methods Data were taken from the 2009 and 2014 Socio-Economic Panel conducted in Germany, and from the 2009 and 2014 European Health Surveys in Spain. The health services investigated were physician consultations and hospital admissions, and the measure of socioeconomic position used was household income. The magnitude of the relationship between socioeconomic position and the use of each health service in people from 16 to 74 years old was estimated by calculating the percentage ratio using binary regression. Results In Germany, after adjusting for age, sex, and need for care, in the model comparing the two lower income categories to the two higher categories, the percentage ratio for physician consultation was 0.97 (95% CI 0.96-0.99) in 2009 and 0.98 (95% CI 0.97-0.99) in 2014, and the percentage ratio for hospitalization was 1.01 (95% CI 0.93-1.10) in 2009 and 1.16 (95% CI 1.08-1.25) in 2014. In Spain, after adjusting for age, sex, and self-rated health, the percentage ratio for physician consultation was 0.99 (95% CI 0.94-1.05) in 2009 and 1.08 (95% CI 1.03-1.14) in 2014, and the percentage ratio for hospitalization was 1.04 (95% CI 0.92-1.18) in 2009 and 0.99 (95% CI 0.87-1.14) in 2014. Conclusion The results suggest that elimination of the copayment in Germany did not change the frequency of physician consultations, whereas after the restriction of universal health coverage in Spain, subjects with lower incomes had a higher frequency of physician consultations.